Benzylation of heterocyclic N-oxides via direct oxidative cross-dehydrogenative coupling with toluene derivatives. (3rd November 2016) - Wan, L.; Qiao, K.; Sun, X. N.; Di, Z. C.; Fang, Z.; Li, Z. J.; Guo, K.
Abstract : A novel cross-dehydrogenative coupling (CDC) of heterocyclic N-oxides with toluene derivatives has been disclosed. Abstract : A novel cross-dehydrogenative coupling (CDC) of heterocyclic N-oxides with toluene derivatives has been discussed, allowing for the facile synthesis of a broad range of structurally diverse C1-benzyl quinoline N-oxides, isoquinoline N-oxides and pyridine N-oxides, including two methylated quinoline N-oxides in particular. This protocol not only extends the application of toluenes in synthetic organic chemistry, but also offers an alternative method to prepare benzylated heterocyclic N-oxides without any metal involved, which is important in medicinal chemistry.